2015
DOI: 10.1902/jop.2015.150152
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Non‐Surgical Therapy of Inflamed Periodontal Pockets During Maintenance Therapy Using Diode Laser: A Randomized Clinical Trial

Abstract: In periodontal maintenance patients, SRP + L did not enhance clinical outcomes compared to SRP alone in the treatment of inflamed sites with ≥ 5 mm PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 40 publications
1
51
0
1
Order By: Relevance
“… There is no evidence that dark pigment‐producing bacteria create such pigments in the human periodontal pocket. Thus, at this point, claims regarding the targeting of black/brown pigmented bacteria in situ by the diode laser must be viewed with skepticism. There is no evidence that the diode laser used as a monotherapy or adjunctive to scaling and root planing is capable of “sterilizing” a periodontal pocket. There is a developing body of evidence indicating that low‐level‐light therapy can be of benefit regarding healing of periodontal tissues, but as yet the evidence is insufficient to allow establishment of protocols or parameters for routine application in clinical practice. There is little to no evidence supporting the use of the diode laser either as a monotherapy or adjunctive to scaling and root planing for the treatment of periodontitis . As stated by Dederich : “With consistently beneficial results from adjunctively using the diode laser not being demonstrated, it then becomes moot to speculate on potential mechanisms of claimed benefits by proponents of this technique.” …”
Section: Summary Of Diode Lasers and Periodontal Therapymentioning
confidence: 99%
“… There is no evidence that dark pigment‐producing bacteria create such pigments in the human periodontal pocket. Thus, at this point, claims regarding the targeting of black/brown pigmented bacteria in situ by the diode laser must be viewed with skepticism. There is no evidence that the diode laser used as a monotherapy or adjunctive to scaling and root planing is capable of “sterilizing” a periodontal pocket. There is a developing body of evidence indicating that low‐level‐light therapy can be of benefit regarding healing of periodontal tissues, but as yet the evidence is insufficient to allow establishment of protocols or parameters for routine application in clinical practice. There is little to no evidence supporting the use of the diode laser either as a monotherapy or adjunctive to scaling and root planing for the treatment of periodontitis . As stated by Dederich : “With consistently beneficial results from adjunctively using the diode laser not being demonstrated, it then becomes moot to speculate on potential mechanisms of claimed benefits by proponents of this technique.” …”
Section: Summary Of Diode Lasers and Periodontal Therapymentioning
confidence: 99%
“…[10][11][12] In contrast to this, few studies found no additional effects of lasers. 37,38 Meta-analysis/systematic reviews also showed no additional effect of laser. 39,40 These changes in the results may be due to small sample size, difference in the definitions considered for classification of the disease, use of different laser system and its parameters.…”
Section: Discussionmentioning
confidence: 99%
“…None of these average differences, regardless of clinical parameter, can be considered as clinically significant. 48,49 Reductions in subgingival bacterial loads were insignificant because four 16,18,23,28 of the seven diode studies did not measure this effect. Of the remaining three studies, only one favored treatment by SRP + adjunctive laser, and two studies detected no significant differences between the test groups.…”
Section: The Datamentioning
confidence: 99%
“…Table 1 shows only seven 16‐19,23,24,28 of the 21 human clinical studies involving a diode laser that may be considered to be without bias. The summary of these seven studies shows that 236 patients participated in the studies (an average of 33.7 patients per study).…”
Section: The Datamentioning
confidence: 99%
See 1 more Smart Citation